2018
DOI: 10.1002/hpm.2534
|View full text |Cite
|
Sign up to set email alerts
|

Collaborate across silos: Perceived barriers to integration of care for the elderly from the perspectives of service providers

Abstract: Health care and social care service providers recognise the need for collaborative work to enhance continuity of care and ageing in place; however, their efforts are hindered by the identified barriers that need to be dealt with in practical terms and by a change of policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Concerns of negatively impacting quality of care when following established structures, are also expressed in this study, urging towards structural changes in future. This is in line with the literature on the importance of care integration to improve channels of communication between providers and generate better care outcomes, also through user empowerment [23][24][25].…”
Section: Integration Coordination and Cooperation Across Ltc Structusupporting
confidence: 88%
“…Concerns of negatively impacting quality of care when following established structures, are also expressed in this study, urging towards structural changes in future. This is in line with the literature on the importance of care integration to improve channels of communication between providers and generate better care outcomes, also through user empowerment [23][24][25].…”
Section: Integration Coordination and Cooperation Across Ltc Structusupporting
confidence: 88%
“…In summary, although there were various practices and providers of EOL care in Hong Kong, as summarized in the Introduction section, there is no overarching policy framework related to EOL care that conceptualizes and clarifies patients’ and their family members’ holistic needs, and how they could be provided with a comprehensive system of care. An advantage of the present study is that it extended from previous works that focused primarily on perspectives from the care providers [ 33 , 34 ]. While there are consistent findings, the present study also encompasses opinions and observations of other major stakeholders of EOL care including the non-care providers.…”
Section: Discussionmentioning
confidence: 99%
“…They found that divergent perceptions of collaboration hindered collaboration between different policy sectors. Diverging perceptions, especially connected to ownership, were also noted as a problem in a recent study focusing on collaboration between health care and social care for elderly populations . They identified different perceptions of ownership as one of the barriers hindering collaboration; these differences were particularly linked to the different values and understandings of the different professions in the different sectors.…”
Section: Discussionmentioning
confidence: 89%